Evaluación de la contaminación acústica generada por las fuentes fijas y móviles en la parroquia Leonidas Plaza del cantón Sucre, provincia de Manabí - Macías Loor, Elian Rene (2025)
Noise pollution is one of the most relevant urban environmental problems due to its effects on human health and quality of life. This study aimed to evaluate the sound pressure levels generated by fixed and mobile sources in the Leonidas Plaza parish, Sucre canton, Manabí province. A non-experimental, quantitative, and descriptive approach was applied. Techniques included direct observation, sound level measurements, resident surveys, and georeferencing to develop noise maps. A total of 268 fixed sources were identified, along with high vehicle traffic during peak hours, with vehicular traffic being the main source of noise. The measurements revealed that in commercial, hospital-educational, and mixed-residential zones, sound pressure levels exceed the limits set by national regulations (TULSMA), especially at midday and in the afternoon, reaching up to 73.58 dBA in certain areas. Additionally, 87% of respondents reported being affected by noise. Based on the findings, a mitigation plan was proposed, structured around sound pressure control, environmental education, and community well-being programs, aiming to reduce acoustic impact and strengthen local environmental management. It is concluded that the Leonidas Plaza parish urgently requires measures to control noise pollution through stricter urban planning, active citizen participation, and effective enforcement of current regulations.